Studying the composition of iodine-rich Khaudak and Uchkizil underground brines in the southern regions of Uzbekistan based on x-ray fluorescence analyzer - Uralov, N.B.; Turaev, Kh.Kh.; Toshkulov, A.X.; Normurodov, B.A.; Umbarov, I.A.; Kurbonov, F.B. (Recent Contributions to Physics, 2025)
This study investigates the underground brines of Khaudak and Uchkizil in southern Uzbekistan, which are rich in various mineral salts, including iodine. The chemical composition of these brines and their time-dependent transformations under environmental exposure were analyzed using X-ray fluorescence spectroscopy (XRF). The results demonstrate that iron compounds present in the brine gradually precipitate over time. The original iron content of the water was approximately 0.130%, with up to 65% of it forming sediment. Additionally, upon adding specific iodine oxidizing agents and storing the sample for one month, a reddish-brown precipitate was formed. This precipitate mainly consisted of iron and chlorine compounds, with minor contributions from iodine and similar elements. The precipitate contained 1.317% iodine, corresponding to 7.66% (21.32 mg/L) of the total iodine in the Khaudak water sample. Exposure to ultraviolet radiation caused further oxidation and volatilization of iodine into the atmosphere. These findings emphasize the importance of timely iodine separation for recovery from brines under natural and controlled conditions.